Work status congruence, work-related attitudes, and satisfaction with worklife balance of services employees in Malaysia / Muhamad Khalil Bin Omar - Omar, Muhamad Khalil (2014)

(untitled)
This study tested whether the relationship between work status congruence and work-related attitudes (i.e., job satisfaction and affective commitment) is mediated by satisfaction with work-life balance. The study also examined the extent to which job satisfaction mediates the relationships between work status congruence and affective commitment, as well as between satisfaction with work-life balance and affective commitment. All measures were adopted from the work of past authors. The items were altered slightly to reflect the references to all non-standard work arrangements (e.g. part-time, temporary, and contract) and life domains apart from family only (e.g. leisure, study, recreation, travel, social, community, and hobbies). This study was conducted using the survey method and 893 services employees in Malaysia participated in this study. The IBM SPSS Statistics 18.0 was used to perform the item-total correlations analysis, exploratory factor analysis (EFA), reliability test, correlation analysis, independent samples t-test and one-way analysis of variance (ANOVA). The IBM SPSS AMOS 18.0 was also used to test the hypotheses of this study. The SEM analysis showed that work status congruence had direct and indirect effects (i.e. via the mediating role of satisfaction with work-life balance) on employees’ work-related attitudes (i.e. job satisfaction and affective commitment). At the same time, work status congruence and satisfaction with work-life balance were found to have direct and indirect effects (i.e. via the mediating role of job satisfaction) on employees’ affective commitment. The findings suggested that the employees’ congruent preferences for work status, schedule, shift and hours could influence their affective commitment through the mediating roles of their satisfaction with their work-life balance and their overall jobs. In other words, this study affirmed that when employees were working on their preferred work staffing and scheduling iv arrangements, they would be satisfied with the balance between their work and nonwork interactions, in terms of their overall jobs; in turn they would be affectively committed towards their organisations. This study is the first in Malaysia to highlight the importance of work status congruence in positively predicting employees’ satisfaction with work-life balance and simultaneously operationalised it among both standard and non-standard employees. Further, extending the applicability of the discrepancy theory conceptualised as workstatus congruence in overcoming the discrepant findings in previous under-developed studies of work-life balance, this study also extended conception of work-family balance by verifying the satisfaction with work-life balance as the mediating mechanism in the relationship between work-status congruence and work-related attitudes. Furthermore, this study attested a unitary measurement of satisfaction with work-life balance, thus, contributed towards the body of knowledge of work-life balance that lacks theoretical studies and conclusive measurement. Therefore, this study provided empirical evidences for both researchers and managers to make references in terms of the importance of employees’ congruent preferences of work-life balance policies, such as non-standard staffing and scheduling arrangements in determining employees’ work-life balance, job satisfaction and affective commitment. Taken together, this study proved that non-standard employment is not a sub-standard employment as long as its implementation is in accordance to employees’ preferences.